Rediseño de red de distribución de aire comprimido en Planta Geotérmica Pailas I - Ramírez-Zamora, Dumas (Instituto Tecnológico de Costa Rica, 2018)
This report presents the analysis of the present situation of the compressed air network in the Pailas I Geothermal Plant, located in Curubandé, Liberia, furthermore the redesign proposed for said network. The reason for the development of the project arises from the need on the part of the electrical, instrumentation and control area to correct a deficiency in the design of the compressed air network, which due to its linear configuration sometimes does not reach the air required to operate the instruments at the end of the line and causes unscheduled stoppages in the electricity generating units. The analysis includes a survey of the current network plan, checking speeds, pressure losses and diameters in all sections; also, the capacity of the air storage tank and the selection of compressors, filters and regenerative air dryer; this to determine the cause of the problem and the proposed solution. Likewise, the project includes the recommendations or improvements that must be made to the network and the price of the elements to be installed. The investment of ¢ 10 466 752 is presented with an IRR of 13.27% due to the saving of avoiding unscheduled stoppages, but which could also be paid thanks to a saving for correction of leaks in the same network compressed air. Furthermore, the project has an environmental impact by contributing to the generation of renewable energy that is based on the National Electric System. The implementation of this project will take place in the year 2020.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018.
Keywords: Aire; Rediseño; Electricidad; Control; Presión